BUGIS NARRATIVE TEXT WRITING SKILLS USING LONTARAK SCRIPT IN CLASS VIII STUDENTS OF SMP NEGERI 1 LABAKKANG PANGKEP REGENCY - Fadel Muh Tamrin; Andi Agussalim AJ; Nurhusna (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This study aims to describe the skills of writing Bugis narrative texts using lontarak script of class VIII students of SMP Negeri 1 Labakkang, Pangkep Regency. This type of research is quantitative research. The population in this study were all class VIII students of SMP Negeri 1 Labakkang, Pangkep Regency, totaling 230 people consisting of 9 classes. The sample of this study was 144 samples, using sample determination with the Krec jie and Morgan tables. Data collection in this study was carried out using test techniques on the research sample. All data obtained were analyzed through several stages: 1) making a list of raw scores, 2) making frequency distributions and raw scores, 3) calculating the average value of students, 4) determining the results of the study with the criteria for the quality of student skills, 5) classifying student skills based on the specified references. Based on the results of the analysis obtained, it shows that the skills of writing Bugis narrative texts using the lontarak script of class VIII students of SMP Negeri 1 Labakkang, Pangkep Regency, namely obtaining a score of 75-100 as many as 57 students, while those who obtained a score of 0-74 were 87 (60%) out of 144 samples, thus the skills of writing Bugis narrative texts using the lontarak script of class VIII students of SMP Negeri 1 Labakkang, Pangkep Regency are categorized as unskilled.